A Bibliometric Study of LIS Literature Related to Academic Law Librarianship - Parks, James Stephen (Qualitative and Quantitative Methods in Libraries, 2017)
Academic law librarianship as a career has experienced an increase in expectations as law librarians have become more closely intertwined with the scholarly mission of today’s law school. A bibliometric analysis of library and information science literature pertaining to academic law librarianship supports this idea as each year more academic law librarians are publishing articles covering a wide range of complex issues faced by all law libraries.  The number of scholarly articles per year increased over the time frame of this study as well as the average number of authors per article. The results of this study identified three core journals that published most of the articles on this topic: Law Library Journal, Legal Information Management, and Legal Reference Services Quarterly.